2010
DOI: 10.1080/17588928.2010.493971
|View full text |Cite
|
Sign up to set email alerts
|

Overclaiming and the medial prefrontal cortex: A transcranial magnetic stimulation study

Abstract: The tendency to claim more knowledge than one actually has is common and well documented; however, little research has focused on the neural mechanisms that underlie this phenomenon. The goal of the present study was to investigate the cortical correlates of overclaiming. Transcranial magnetic stimulation (TMS) was delivered to the medial prefrontal cortex (MPFC), supplementary motor area, and precuneus during the presentation of a series of words that participants were told made up a cultural IQ test. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…We have previously found using a similar paradigm that the response rate of ‘knowing’ words is not different between fake and real words, which results in a significant amount of false positives [ 5 ]. Similar to Palhaus’s findings [ 33 , 34 ], we conclude that faking knowledge is socially mediated and that the risk of being seen not knowing something is greater than claiming to know something that you do not.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously found using a similar paradigm that the response rate of ‘knowing’ words is not different between fake and real words, which results in a significant amount of false positives [ 5 ]. Similar to Palhaus’s findings [ 33 , 34 ], we conclude that faking knowledge is socially mediated and that the risk of being seen not knowing something is greater than claiming to know something that you do not.…”
Section: Discussionmentioning
confidence: 99%
“…The MPFC plays a critical role in testing reality [ 19 , 38 ], self-knowledge [ 39 , 40 ] and more specifically for this study, falsifying one’s reported knowledge [ 5 ], abilities and traits [ 29 ] as well as monitoring social reactions of others in regards to the self [ 41 ].It is therefore not surprising to observe disruption of the MPFC has an influence on false responding. Because TMS had an influence on fake words, but not real words, we speculate that disruption of the MPFC is not uniform in its cognitive influence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations